We are driven : the compulsive behaviors America applauds - Hemfelt, Robert; Minirth, Frank B.; Meier, Paul D. (Nashville : T. Nelson, 1991)
Rather than "be all we can be," the authors strive to help each of us who are susceptible to the drivenness which society values, but are actually deadly, live-damaging addictions.
Unmasking the compulsions America applauds. Are we really having fun? -- The many masks of compulsions -- Learning to say "Ouch!" -- Riding a bike without a chain -- Breaking the cycle. Events that set the cycle in motion : Family of origin or major life trauma -- Sinister whispers from the past : Negative messages -- The shame that binds : The shame base -- Driven to be more to keep from being less : Low self-esteem -- The devastating boomerang : The "Ouch!" of emotional pain -- Our false gods : The addictive agent -- The billion-dollar price tag : Fallout -- The split personality : Violation of values -- Guilty! : Guilt -- Recovery. Touchstones for living a balanced life.
Includes bibliographical references (pages 317-320).
Keywords: Compulsive behavior -- Popular works; Compulsive Behavior -- Popular Works; Popular works